Relationship Between Students' Mathematical Representation Ability And Self-Confidence - Fitri, Fitri; Kartini, Kartini; Suanto, Elfis (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
This research is motivated by the students' self-assurance in the acquisition of mathematics and their limited mathematical representation ability. The objective of this study is to examine the relationship between self-assurance and mathematical representation skill with the goal of utilising it as a model to improve mathematical representation ability. The research investigated the capacity for mathematical representation in terms of verbal and visual representation. Correlational quantitative research is implemented in this investigation. A self-confident questionnaire and a written exam of mathematical representation ability were implemented as the data collection methodology. The subjects they studied were those of the ninth-grade students at SMP Muhammadiyah 4 Pekanbaru. Self-confident questionnaires were disseminated to gather data, and the mathematical representation ability test was administered in the form of description questions. The impact of self-confidence on learning outcomes is 91.6%, as indicated by the results of simple linear regression and simple correlation analysis. The learning outcomes of mathematical representation are influenced by 8.4% of other variables and are not specific to this case.